(untitled) (Czech Journal of International Relations, 1999)
In 1997–1998, Ukraine was described with increasing frequency as the key factor of stability in the new Europe. For objective reasons, Ukraine cannot attempt to become a world power but it can become a significant regional factor. However, long-term and stable national and state interests, mainly economic and social, must become the foundations of its policy. And it is precisely from this point of view that the pattern of its endeavours to promote cooperation with countries around the Black and Caspian Sea must be seen; the objective of these endeavours is to consolidate the national energy security and to diversify the sources of energy raw material supplies (mainly oil) in such a way that the country should extricate itself from exclusive dependence on oil supplies from Russia. This applies first and foremost to the Ukrainian-Turkish project of the Ceyhan-Samsun pipeline, part of which i s also the construction of the Odessa oil terminal and the Odessa-Brody-Adamowa zastawa pipeline. Ukraine is, furthermore, a significant oil transit country to Central and Western Europe, since two systems of transit pipelines – the Druzhba and the Pridnepetrovskaja – lead across its territory; more than half of all Russian oil exports flow through these systems every year. In addition, the Ukrainian-Hungarian ethylene pipeline and one branch of the product pipeline for the transportation of finished oil products also lead across this territory. In actual fact, the Ukrainian problem does not boil down to the sources from which energy raw materials (mainly oil) can be extracted but how to pay for them. Ukraine nowadays lacks resources and that is why it would prefer to pay for its supplies in the form of transit services. Even attempts by the Ukrainian government to privatize the biggest state refineries were unsuccessful. Yet, the capacity of Ukrainian refineries is not fully exploited, their equipment is obsolete, and because of a shortage of finances the extraction of the country’s own oil is not even being developed.